Significance of Hindu Pilgrimage; study of Pashupathinath and Kashi Vishwonath (Patan Pragya, 2020)
Pilgrimage is one of the most common phenomena found in religious culture, occurring in just about every major religious tradition. Pilgrimage has adapted to a purportedly secularizing world, and even benefited from contemporary modes of transportation and communication. All pilgrims provide the message of human welfare, development of universe and religious and spiritual promotions for the welfare of society, way to truth, salvation and many more through interactions, observations of pilgrimage, but for understanding the cultural system in both intrinsic and extrinsic ways, or as insider and outsider, a human science paradigm would be better as it covers the totality thus attempting to reveal the “whole” of the culture, human psyche and functions at play.  It was found that no any kind of discriminations, differences, inequalities on the basis of caste, class, gender, ethnicity etc. among pilgrimage during the visit. Almost all respondents felt the harmony, cohesion and friendly during the visit though cross-border. All Shiva shrines promote the welfare of animals, human and the world. Harmony, cohesion, solidarity and brotherhood and sisterhood were found good. Any kind of discriminations, differences, inequalities were not found on the basis of caste, class, gender, ethnicity etc.